2019
DOI: 10.1111/adj.12727
|View full text |Cite
|
Sign up to set email alerts
|

Think before you prescribe: how dentistry contributes to antibiotic resistance

Abstract: Antibiotic resistance presents a daunting challenge to health professionals worldwide and has the potential to create major problems for modern health care, resulting in more medical expenditure, extended hospital stays and increased morbidity and mortality. Advanced genome sequencing technologies present a complex picture of resistance, extending our understanding beyond the pharmacotherapeutic interface between pathogens and antibiotics. This review discusses the global scope and scale of antibiotic resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…On the other hand, the risk of these undesirable effects is cumulative and related to increased exposure [ 16 ]; this overprescription promote the proliferation of antibiotic-resistant bacteria [ 10 , 13 , 15 , 17 , 18 ]. Moreover, it has been reported that 66% of antibiotics prescribed in connection with dental procedures are not clinically indicated [ 19 ] because bacterial cultures and sensitivity tests are rarely performed; therefore, broad-spectrum antimicrobials are prescribed as a result of non-evidence-based assumptions [ 20 ]. This proves all the more important when it is estimated that 10% of antimicrobials are prescribed by dentists [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the risk of these undesirable effects is cumulative and related to increased exposure [ 16 ]; this overprescription promote the proliferation of antibiotic-resistant bacteria [ 10 , 13 , 15 , 17 , 18 ]. Moreover, it has been reported that 66% of antibiotics prescribed in connection with dental procedures are not clinically indicated [ 19 ] because bacterial cultures and sensitivity tests are rarely performed; therefore, broad-spectrum antimicrobials are prescribed as a result of non-evidence-based assumptions [ 20 ]. This proves all the more important when it is estimated that 10% of antimicrobials are prescribed by dentists [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic complications with antibiotic usage include anaphylaxis, development of resistant strains, interaction with other medicines, and side effects, including nausea, vomiting, diarrhea, and pseudomembranous colitis [ 22 , 31 ]. These adverse effects are a major cause of morbidity and mortality for patients [ 11 , 36 ]. The frequent comment from practitioners of ‘better healing’ associated with the use of antibiotics noted in this survey may reflect a tendency to prescribe antibiotics, despite risks of adverse effects, in an attempt to aid wound healing post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as the appropriate, safe, and discriminate use of antimicrobials for therapy and prophylaxis, antibiotic stewardship has been championed by governments, international health organizations, and initiatives to reduce issues associated with antibiotic-resistant pathogens [ 4 , 11 ]. With regards to following the principles of antibiotic stewardship, dental practitioners may be falling short.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations